2022
DOI: 10.3390/antibiotics11010059
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Antimicrobial, Antioxidant, and Anticancer Studies of Leaf Extract of Simarouba glauca DC In Vitro

Abstract: The current study aimed to screen the preliminary phytochemicals in the leaf extract of the medicinal plant Simarouba glauca and to analyze its potential antimicrobial, antioxidant and anticancer properties. The phytochemical profile of the methanol extract was analyzed, and bioactive compounds were identified using chromatography, FTIR and GCMS. Antimicrobial activity and Minimum Inhibitory Concentration (MIC) were determined against 14 bacterial and 6 fungal strains. Moreover, the synergistic effect of a pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Cellular debris in the surroundings of the cells were also visible after treatment. Ramasamy et al [85] also reported the disintegration of cellular structure after treatment with plant extract.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Cellular debris in the surroundings of the cells were also visible after treatment. Ramasamy et al [85] also reported the disintegration of cellular structure after treatment with plant extract.…”
Section: Discussionmentioning
confidence: 96%
“…Prepared P. betle extracts were evaluated for the presence of various phytochemical compounds (steroids, alkaloids, phenolic compounds, saponins, flavonoids, tannins, terpenoids, carbohydrates, and glycosides) by standard tests [85,94,95]. 4.6.…”
Section: Phytochemical Screening Of P Betle Extractmentioning
confidence: 99%
“…Bitki ekstrelerinin antikanser etkilerinin in-vitro olarak incelenmesine yönelik çalışmalarda son yıllarda bir artış yaşanmaktadır. Ramasamy ve çalışma arkadaşları Simarouba glauca yaprağı ekstresinin MCF-7 meme kanser hücreleri üzerinde 16.12 µg/mL IC50 değeri ile önemli sitotoksik etki gösterdiğini rapor etmişlerdir (20). Kanash ve çalışma ekibi 1000 µg/mL Dovyalis caffra meyvesi ekstresi uygulanan HepG2 karaciğer kanser hücrelerinde % canlı hücre oranının %41,10'a düştüğünü bildirmişlerdir (21).…”
Section: Discussionunclassified
“…Protein content was quantified by the Biuret method as previously described [ 62 ]. In brief, overnight cultures of A. baumannii isolates (before and after treatment with SAME at 0.5 MIC values) were incubated for 24 h at 37 °C in a shaker incubator.…”
Section: Methodsmentioning
confidence: 99%